Development macroeconomics - Agénor, Pierre Richard (Princeton University, 1996)
This book provides an in-depth review of the main contributions of the last two decades in the macroeconomics of developing countries. Its presentation of the state of knowledge in this area strikes a very good balance between intuitive and analytical discussion, and is weel motivated by constant references to the contemporary macroeconomic problems faced by policymakers in developing nations.